Infliximab-induced remission improves physical activity in patients with active Crohn's disease - Lucca,Fernando de Azevedo (2020)
SUMMARY AIM: To compare the level of physical activity (PA), exercise capacity, and body composition before and after infliximab-induced clinical remission in patients with Crohn's disease (CD). METHODS: This prospective longitudinal study evaluated 44 adult outpatients with active CD before infliximab administration and 24 weeks after infliximab therapy. The patients were evaluated for PA in daily life, exercise capacity, muscle strength, and body composition. RESULTS: 38 (86.4%) patients achieved infliximab-induced remission at 24 weeks and presented an increment in the number of steps taken of 1092 (7440±2980 vs. 6348±3177, respectively; p=0.006). The inactive time was reduced when compared to the baseline value (454.2±106.3 vs. 427.9±97.8, respectively; p=0.033). There was no difference in the distance walked before and after infliximab therapy, while there was an increase in the fat mass index in responders to infliximab compared to the baseline (19.1±7.6 vs. 14.9±5.8; p=0.001). CONCLUSIONS: Infliximab-induced remission was shown to be effective for increasing physical activity by improving the number of steps and reducing inactive time. The maintenance of clinical remission associated with incentives to regular PA may contribute to making these patients reach an ideal level of PA.